Capital Market Reaction to Free Nutritious Food Policy: A Case Study of Palm Oil Companies on Indonesia Stock Exchange - Jihan Eka Putri; Muhammad Nofal; Husnah Husnah; Rian Risendy (Dinasti Publisher, 2025)
The Free Nutritious Meal Policy, targeted at school students, toddlers, and pregnant women, is implemented as an effort to reduce stunting and produce high-quality human resources. The reaction of investors in the capital market to this program remains unknown, even though the program directly increases the volume of food that will be consumed, such as palm cooking oil. Therefore, this research aims to test whether investors react to the MBG program by analyzing the abnormal returns of palm oil company stocks that are expected to receive direct positive impacts from the program. To this end, we examine this market reaction by conducting an event study based on the market model. The analysis utilizes return data from 24 palm oil company stocks listed on the BEI. We found that positive and significant abnormal returns occurred a few days before and after the event date, indicating an investor reaction to the MBG program. The variable abnormal returns suggest that the market reaction tends to be slow and spreads gradually and indirectly. The inconsistency in significant patterns indicates that market information is still developing, while also reflecting investors' cautious attitude toward government policies with broad impacts.